Tess of the D'Urbervilles - Hardy, Thomas, 1840-1928. (Mineola, N.Y. : Dover, 2001)
A young woman finds herself the victim of fate and of forces beyond her control in nineteenth-century England.
Originally published: New York : Macmillan Co., 1912.
Adult
Keywords: Children of clergy -- Fiction; Children of the rich -- Fiction; Man-woman relationships -- Fiction; Poor families -- Fiction; Triangles (Interpersonal relations) -- Fiction; Women household employees -- Fiction; Women murderers -- Fiction; Clergy -- Fiction; Didactic fiction; Family life -- Fiction; Man-woman relationship -- Fiction; Pastoral fiction; Poor -- Fiction; Rich -- Fiction; Triangles (Interpersonal relations) -- Fiction; Women household employees -- Fiction; Women murderers -- Fiction; Wessex (England) -- Fiction; Wessex (England) -- Fiction; Didactic fiction; Pastoral fiction